Sikap politik perempuan pada Pemilu legislatif tahun 2019 - Sekar Ndini, Ayu; M. Japar; Martono, Agus (Universitas Airlangga, 2024)
This study aims to obtain empirical data about the relationship between political attitudes and women's political participation in the 2019 legislative elections. The method used is explanatory research methods. The population of this study was 241 and the sample used was 84 people from 20% of the population. The sampling technique uses simple random sampling. The product-moment correlation hypothesis test that produces a correlation coefficient of 0,429 and r-table for 84 respondents is 0,215 with a confidence level of 95%. With the coefficient of determination obtained at 18,4%. In conclusions, there is a positive relationship between political attitudes and women's political participation in the 2019 legislative election at Srengseng, Kembangan, West Jakarta.